ECONOMIC PLANNING AND THE ROLE OF RENEWABLE ENERGY IN REDUCING CARBON FOOTPRINT - Hiren chandrakant Pathak (IJRDO - Journal of Electrical And Electronics Engineering, 2021)
There is a growing reliance on economic planning on matching growth with environmental restraint. Renewable energy is a viable solution to the uncoupling of development and emissions by a broader portfolio on energy and price stabilisation as well as spurring productivity through innovation. Policymakers continue to have a confused body of evidence on how strategic planning transforms energy transitions into enshrined carbon impacts without compromising competitiveness. This paper is a synthesis of both cross-country policy research and panel-based econometric analysis based on thirty years of data on the energy mix, industrial structure, and the quality of governance. We overlay policy tools, objectives, market incentives, and government–corporate finance and evaluate consistency between fiscal structures and climate policies. It suggests that a policy-based long-term growth in renewables is associated with quantifiable reductions in the intensity of carbon emission and enhanced macroeconomic stability. A grid upgrade, flexibility services and workforce programme planning enhances clean technologies spread. The spillovers in the manufacturing, transport, and buildings are enhanced by complementary measures, standards, carbon budgeting, and mission-oriented research. The best approach to incorporating renewables into economic planning is through institutions aligning both long-term investment indicators with the short term affordability and reliability guarantees. Open administration, trustworthy schedules, as well as adaptive regulations decrease risk premiums, draw funds and normalise low-carbon decisions by firms and households. Nations integrating learning systems and equity experiences have a more stable process and extend social licence. Sequencing, constant re-evaluation and flexible design turn the adoption of renewable energy into sustainable, system-wide decarbonisation and stable, opportunity-based growth. The literature indicates that there is an integrated planning between energy, industry, and skills policy in frameworks.